2011
DOI: 10.1007/s00109-011-0725-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of 51 unrelated pedigrees with late-onset multiple acyl-CoA dehydrogenation deficiency (MADD) in southern China confirmed the most common ETFDH mutation and high carrier frequency of c.250G>A

Abstract: Multiple acyl-CoA dehydrogenation deficiency (MADD) is an autosomal recessive disease affecting amino acid, fatty acid, and choline metabolisms and is a common genetic defect responsible for lipid storage myopathy. Most forms of MADD are caused by a deficiency of electron transfer flavoprotein (ETF) or ETF dehydrogenase (ETFDH). However, its molecular feature has not been found uniformly in previous reports of Chinese patients. A large cohort of 56 late-onset MADD patients from 51 unrelated pedigrees in southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 28 publications
12
57
0
Order By: Relevance
“…The mean age at onset of 146 patients with late-onset MADD of whom detailed information was given in the literature is 14.3 years. Of additional 56 cases reported by Wang et al [[55]] and 71 cases reported by Xi et al [[28]] only the mean age at onset (24.5 ± 12.6 years with a range from 4 to 55 years and 25.0 ± 13.3 years with a range from 4 to 36 years, respectively) is known. If these cases are also taken into account, the mean age at onset in this study cohort is 19.2 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age at onset of 146 patients with late-onset MADD of whom detailed information was given in the literature is 14.3 years. Of additional 56 cases reported by Wang et al [[55]] and 71 cases reported by Xi et al [[28]] only the mean age at onset (24.5 ± 12.6 years with a range from 4 to 55 years and 25.0 ± 13.3 years with a range from 4 to 36 years, respectively) is known. If these cases are also taken into account, the mean age at onset in this study cohort is 19.2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Most mutations seem to be private. Three common mutations in the ETFDH gene have been described which are mainly found in the Chinese and Taiwanese population: c.250G > A (p.A84T), c.770A > G (p.Y257C), c.1227A > C (p.L409F) [[23],[28],[55]]. As this literature review has shown, the vast majority of late-onset patients harbour mutations in the ETFDH gene, while ETFA or ETFB mutations are found in only about 7% of individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the carrier frequency of c.250G > A is estimated to be 1.35% amongst the population in southern China. Thus, ~1:22,000 Han Chinese are expected to suffer from riboflavin-responsive MADD [7]. Intriguingly, p.Ala84Thr has been identified in Asian countries including Taiwan, Hong Kong, Singapore, Thailand and southern China [6-11].…”
Section: Introductionmentioning
confidence: 99%
“…Acute metabolic crisis can be lethal when it is severe. Gastrointestinal symptoms, including abdominal pain, vomiting, diarrhea and hepatomegaly, are frequently observed . Cardiomyopathy and brain involvement have also been reported in MADD …”
Section: Clinical Featuresmentioning
confidence: 99%